To Philosophize or not to Philosophize? Rorty's Challenge to Feminists - Marianne Janack (Ideas y Valores)
This article takes up Rorty's advice to feminists to abandon philosophizing (and appeals to truth and reality) in favor of using language to create a new logical space for feminist politics. The argument focuses on the rhetorical role of appeals to truth and reality, the role of linguistic innovation in social change, and the feminist critique of Rorty's use of the "prophetic voice" in his discussion of feminist politics.